Assessment of the Correlation Between Insertion Torque and Resonance Frequency Analysis of Implants Placed in Bone Tissue of Different Densities - Magno Filho, Luiz Carlos [UNESP]; Cirano, Fabiano Ribeiro [UNESP]; Hayashi, Fernando [UNESP]; Feng, Hsu Shao [UNESP]; Conte, Alexandre [UNESP]; Dib, Luciano Lauria [UNESP]; Casati, Marcio Zaffalon [UNESP] (Allen Press Inc, 2014)
The primary stability of dental implants is fundamental for osseointegration. Therefore, this study aimed to assess the correlation between insertion torque (IT) and resonance frequency analysis (RFA) of implants placed in mandibles and maxillas of different bone densities. Eighty dental implants were placed in maxillas and mandibles, and IT and the implant stability quotient (ISQ) were measured at the time of implant insertion. Bone density was assessed subjectively by the Lekholm and Zarb index. The type I and II densities were grouped together (group A)as were the type III and IV densities (group B). The IT in group A was higher (Student t test, P = .0013) than in group B (46.27 +/- 18.51 Ncm, 33.62 +/- 14.74 Ncm, respectively). The implants placed in group A showed higher ISQ (Student t test, P = .0004) than those placed in group B (70.09 +/- 7.50, 63.66 +/- 8.00, respectively). A significant correlation between IT and the ISQ value was observed for group A (Pearson correlation test; r = 0.35; P = .0213) and for group B (r = 0.37; P = .0224). Within the limitations of this study, it was possible to conclude that there is a correlation between IT and RFA of implants placed in mandibles and maxillas of different bone densities.
Keywords: insertion torque; dental implant; bone density; RFA